The efficacy of various bait products against the grey field slug Deroceras reticulatum - Howlett, S.A.; Wilson, D.J.; Miller, K.T. (New Zealand Plant Protection, 2008)
The grey field slug Deroceras reticulatum is one of the most dominant slug pests in temperate climates In mild moist conditions populations can rapidly reach economically damaging levels Largescale control relies heavily on the use of molluscicide baits The active ingredients in molluscicides are often in themselves repellent to slugs and must be formulated with other more palatable substances to ensure sufficient ingestion A study was undertaken to compare the efficacy of four bait products at various time intervals after application to bare soil Slug morbidity following bait application 48 h prior to exposure was significantly higher for methiocarb products while metaldehyde products experienced reduced efficacy after the same time period